SynergiCity : reinventing the postindustrial city - Kapp, Paul Hardin; Armstrong, Paul J. (University of Illinois Press, 2012)
"SynergiCity: Reinventing the Postindustrial City proposes a new and invigorating vision of urbanism, architectural design, and urban revitalization in twenty-first-century America. Culling transformative ideas from the realms of historic preservation, sustainability, ecological urbanism, and the innovation economy, Paul Hardin Kapp and Paul J. Armstrong present a holistic vision for restoring industrial cities suffering from population decline back into stimulating and productive places to live and work. With a particular emphasis on the Rust Belt of the American Midwest, SynergiCity argues that cities such as Detroit, St. Louis, and Peoria must redefine themselves to be globally competitive. This revitalization is possible through environmentally and economically sustainable restoration of industrial areas and warehouse districts for commercial, research, light industrial, and residential uses. The volume's expert researchers, urban planners, and architects draw on the redevelopment successes of other major cities--such as the American Tobacco District in Durham, North Carolina, and the Milwaukee River Greenway--to set guidelines and goals for reinventing and revitalizing the postindustrial landscape. Contributors are Paul J. Armstrong, Donald K. Carter, Lynne M. Dearborn, Norman W. Garrick, Mark Gillem, Robert Greenstreet, Craig Harlan Hullinger, Paul Hardin Kapp, Ray Lees, Emil Malizia, John O. Norquist, Christine Scott Thomson, and James Wasley"--